RETRACTED: Mesenchymal Stem/Stromal Cell-Based Delivery: A Rapidly Evolving Strategy for Cancer Therapy - Hassanzadeh, Ali; Altajer, Amjad Hussein; Rahman, Heshu Sulaiman; Saleh, Marwan Mahmood; Bokov, Dmitry O.; Abdelbasset, Walid Kamal; Marofi, Faroogh; Zamani, Majid; Yaghoubi, Yoda; Yazdanifar, Mahboubeh; Pathak, Yashwant; Chartrand, Max Stanley; et al. (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Mesenchymal stem/stromal cell (MSCs)-based therapy has become an attractive and advanced scientific research area in the context of cancer therapy. This interest is closely linked to the MSCs marked tropism for tumors, suggesting them as a rational and effective vehicle for drug delivery for both hematological and solid malignancies. Nonetheless, the therapeutic application of the MSCs in human tumors is still controversial because of the induction of several signaling pathways largely contributing to tumor progression and metastasis. In spite of some evidence supporting that MSCs may sustain cancer pathogenesis, increasing proofs have indicated the suppressive influences of MSCs on tumor cells. During the last years, a myriad of pre-clinical and some clinical studies have been carried out or are ongoing to address the safety and efficacy of the MSCs-based delivery of therapeutic agents in diverse types of malignancies. A large number of studies have focused on the MSCs application as delivery vehicles for tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), chemotherapeutic drug such as gemcitabine (GCB), paclitaxel (PTX), and doxorubicin (DOX), pro-drugs such as 5-fluorocytosine (5-FC), and ganciclovir (GCV), and immune cell-activating cytokines along with oncolytic virus. In the current review, we evaluate the latest findings rendering MSCs potential to be employed as potent gene/drug delivery vehicle for inducing tumor regression with a special focus on the in vivo reports performed during the last two decades.